Code-Switching in Multilingual Classroom Interaction: A Sociolinguistic Analysis of the Sitcom Mind Your Language - Purwanti, Eko; Sugiyanto SY, Hanna Nabila Annas Amini (Ahmad Dahlan Journal of English Studies, 2026)
Code-switching is a common linguistic practice in bilingual and multilingual communities in which speakers alternate between languages to negotiate meaning and maintain communication. This study examines how code-switching is represented in the British sitcom Mind Your Language, a television series that portrays learners from diverse linguistic and cultural backgrounds interacting in an English language classroom. This research aims to identify the types of code-switching used in the series and to explore the communicative purposes behind these language shifts. The study adopts a descriptive qualitative approach by analysing dialogues from two episodes of the first season. The findings reveal that inter-sentential switching is the most frequently occurring type of code-switching in the selected episodes, followed by intra-sentential switching, while tag-switching does not appear in the data. In addition, six communicative motivations for code-switching were identified, with discussing a particular topic emerging as the most dominant reason, followed by expressing emphasis and repetition for clarification. These findings highlight how code-switching functions as a communicative strategy among multilingual speakers and demonstrate how popular media can reflect real-world linguistic practices in multilingual settings.